Reversal of hypertonic co-contraction after bilateral pallidal stimulation in generalised dystonia: a clinical and electromyogram case study. - Liu, X; Tailor, J; Wang, S; Yianni, J; Gregory, R; Stein, J; Aziz, T (2004)
In a patient of generalised dystonia treated with bilateral pallidal stimulation, serial surface EMGs recorded from the neck muscles during alternating head movements revealed progressive reduction in hypertonic activity and reversal of co-contraction to reciprocal contraction, which preceded clinical improvement.